ChemInform Abstract: Nanoparticle Catalyzed Reaction (NPCR): ZnO‐NP Catalyzed Ugi‐Reaction in Aqueous Medium. Issue 8 (25th February 2014) - Kumar, Atul; Saxena, Deepti; Gupta, Maneesh Kumar
Abstract The ecofriendly procedures can be regarded as new methods for the preparation of pharmaceutically relevant phenylacetimidamides (IV), phenylacetamides (V) and α‐amino acid derivatives (VI).